2019
DOI: 10.1177/1756286419864830
|View full text |Cite
|
Sign up to set email alerts
|

Does statin increase the risk of intracerebral hemorrhage in stroke survivors? A meta-analysis and trial sequential analysis

Abstract: Background: It remains debatable whether statin increases the risk of intracerebral hemorrhage (ICH) in poststroke patients. Methods: We systematically searched PubMed, EMBASE, and CENTRAL for randomized controlled trials. Trial sequential analysis (TSA) was conducted to assess the reliability and conclusiveness of the available evidence in the meta-analysis. To evaluate the overall effectiveness, the net composite endpoints were derived by totaling ischemic stroke, hemorrhagic stroke, transient ischemic attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
2
24
0
1
Order By: Relevance
“…A recent study indicated that statin therapy in post-stroke patients increased the risk of hemorrhagic stroke; however, when weighing the benefits and potential harms, statins had an overall beneficial effect in patients with a history of stroke. 51 Therefore, the risk of stroke for elderly patients who are taking statins needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that statin therapy in post-stroke patients increased the risk of hemorrhagic stroke; however, when weighing the benefits and potential harms, statins had an overall beneficial effect in patients with a history of stroke. 51 Therefore, the risk of stroke for elderly patients who are taking statins needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…For statins, these findings are perforce consistent with prior studies, as the data is abstracted from the three most comprehensive meta-analyses of all-patient/all-dose, high dose, and prior ischemic stroke RCTs and the one salient trial for prior hemorrhagic stroke. 3,10,12,13 For each of the meta-analyses, there was no-to-moderate heterogeneity and none with high heterogeneity, indicating good consistency of results across trials. The findings of these meta-analyses contrast with some meta-analyses by other groups that did not find elevated hemorrhagic stroke risk with statins, but those studies were limited by: (1) less comprehensive inclusion of relevant RCTs and (2) analysis not only of RCTs, but also observational studies, which are vulnerable to confounding by indication.…”
Section: Discussionmentioning
confidence: 94%
“…Although these uterine bleeding AEs of statins have not been previously reported, the bleeding risk at other sites associated with statins has already been identified. For example, several epidemiologic studies indicated that statin use was associated with increased risk of intracerebral hemorrhage and gastrointestinal hemorrhage [33][34][35] . The underlying mechanisms by which statins increase bleeding risk may include the following points: first, lower serum cholesterol levels induced by statins may increase risk of rupture and hemorrhage by reducing vessel resistance to tension 36 ; second, statins could inhibit the prenylation of small GTP-binding proteins (GTPases), such as CDC42 and Rac1, resulting in alteration of vascular permeability 37 ; third, statins also have antithrombotic effects, decrease platelet activity, inhibit platelet aggregation, have anticoagulant activity, affect blood viscosity and RBC deformability, and 'improve' von Willebrand factor activity 33 .…”
Section: Discussionmentioning
confidence: 99%